The Decision To Revisit Coffee Drinking Is Seen From The Lifestyle And Attributes Of Coffee Through The Brand Image - Amin Hou; Dahrul Siregar (International Journal of Science, Technology & Management, 2021)
At present, the coffee shop business continues to experience rapid development. The need for coffee changes the lifestyle of a consumer. The main objective of this research is to determine the direct and indirect effect of lifestyle variables and product attributes on purchasing decisions through brand image. This research was conducted at Keude Kupie Ulee Kareng & Gayo II in Medan City. The main target population and sample in this study were the loyal visitors at Keude Kupie Ulee Kareng & Gayo II. Where 175 respondents were selected to be the research sample. The results of the analysis show that the lifestyle and product attributes directly have a significant effect on brand image. Then, indirectly, lifestyle has an indirect effect on purchasing decisions through brand image. Product attributes have an indirect effect on purchasing decisions through brand image.